THE FUTURE OF CONSUMER EXPERIENCE IN A SCIENCE AND TECHNOLOGY PARK – SPACES TO INTERACT - Maldaner, Luis Felipe; Fiorin, Flávia Siqueira; Simon, Luísa (Revista Gestão e Desenvolvimento, 2018)
One of the most important value assigned to an innovation environmental is the dynamic of the network and its interaction. Concerned about that, Tecnosinos’ startups were invited to evaluate and discuss the interaction and communication of the ecosystem in a Design Thinking workshop. The workshop feedback was crucial for Tecnosinos review its strategy and immediately work on the needs appointed. After the event a group actions were address considering three main approaches: communication efforts, event promotion and physical structure. Through a survey to evaluate these approaches, the startups were questioned about the expectation that entrepreneurs had before entering the Park and the experiences they had after joining the Park. As a result, the Parks have the opportunity to play the role of involving and moving the actors to a qualified interaction through its network. Tecnosinos is building, together with the startups and other actors of the ecosystem, a new consumer experience in services. Keywords: Consumer experience. Unitec incubator. Startups. Service. RESUMO Um dos mais importantes valores existentes em um ambiente de inovação é a dinâmica de relacionamentos e suas interações. Nesse sentido, as startups do Tecnosinos foram convidadas a avaliar e discutir a interação e comunicação desse ecossistema num workshop de Design Thinking. O feedback coletado nesse workshop foi crucial para o Tecnosinos rever sua estratégia e imediatamente trabalhar nas necessidades apontadas pelos empreendedores. Após o evento um conjunto de ações foram iniciadas, considerando três principais pontos: esforços de comunicação, promoção de eventos e estrutura física. Através de uma survey que teve por objetivo avaliar a nova estratégia de relacionamento e comunicação, as startups foram questionadas sobre a expectativa que os empreendedores tinham antes de ingressar no Parque e as experiências que eles tiveram depois de integrar o Parque Tecnológico. Como resultado, o Parque teve a oportunidade de liderar o envolvimento e a movimentação dos atores para qualificar a interação através do network. Tecnosinos está construindo, juntamente com as startups e outros atores do ecossistema, uma nova experiência de consumo em serviços. Palavras-chave: Experiência de consumo. Incubadora Unitec. Startups. Serviços.